Heptavalent ARC-transitive cayley graphs on frobenius groups with soluble vertex stabilizer - Liu, Hailin (Utilitas Mathematica, 2020)
A Cayley graph ľ is said to be arc-transitive if its full automorphism group AutT is transitive on the arc set of J1 . In this paper, we give a characterization of heptavalent arc-transitive Cayley graphs on a class of Probenius groups with soluble vertex stabilizer. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.